UJI EFEKTIVITAS ANTIBAKTERI SARI BUAH MENGKUDU (Morinda citrifoliaL.) ASAL MAKASSAR PADA DAGING SAPI - Faridha Yenny Nonci; Rusli Rusli; Jumatia Jumatia (Jurnal Farmasi UIN Alauddin Makassar, 2015)
The experiment has been done about of the inhibition The Effectiveness of Antibacterial Test Noni Juice (Morinda citrifolia.L) From Makassar on Beef. This experiment aims to determine the effectivenes of noni juice can inhibit the growth of bacteria on beef and knowing that the most effective concentration of fruit juice can inhibit the growthof bacteria on beef. Noni juice exstracted mechanically using organoleptic test and than ALT test bacteria on beef with control, concentration 5%, 10%, 15%, 20%, 25% and 50%. Organoleptic tests conducted test smells, textures and colours calculated the total number of bacteria by dilution made from 10-1 to 10-4 and thaninserted into a petri dish countaining medium and incubated for 1 x 24 hours and counted the total number of microbes with the TPC method.The result showed Noni juice can inhibit the growth of bacteria on beef that is at concentrations of 50% which gives any lasting power on beef for three days.Most true god over all creation.